(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
The article examines the legal framework for environmental protection based on international, regional and national standards. Today, ideas are put forward about a fundamental change in our society and in the international arena in the attitude to ecology, the role and significance of ecology in human life. Natural resources and natural and climatic conditions play an important role in each country. They are of great importance for all segments of the population and play a significant role in determining the healthy lifestyle of humanity in the future.